Comprehensive Review of Nutrition Components for Occupational Health Nurses—Part 2. (November 2018) - Chikotas, Noreen; Toothaker, Rebecca
This article, the second in a two-part series, reviews and examines the components of clinical nutrition. In Part 2, the authors discuss nutritional components of fats, proteins, vitamins, minerals, and water. A resource guide is provided for the occupational health nurse to assist in the implementation of employee education in the area of healthy nutrition. The intent of the articles is to acquaint and inform the occupational health nurse on the current guidelines for healthy eating so she or he can better appraise their employee population, thus creating a healthier workforce. The information provided is not all-inclusive on the topics discussed but it provides a foundation for a better understanding of the requirements for healthy eating.